Can SMEs synergistic transformation of digitization and greenization promote enterprise risk-taking? - Juan Wang; Jianxin Cui (PLoS ONE, 2025)
The synergistic transformation of digitization and greenization has become an important direction in China’s economic development. Small and Medium Enterprises (SMEs) have the characteristics of small scale and high growth and have become the key force of synergistic transformation of digitization and greenization. Synergistic transformation of digitization and greenization helps to promote the coordination and unification of SMEs’ operating efficiency and environmental protection, resulting in the effect of 1 + 1 > 2, which has become an important factor in promoting enterprise risk-taking. Using the sample of enterprises listed on the SME board from 2012 to 2022, this paper adopts the Haken model to measure SMEs’ synergistic transformation of digitization and greenization and analyzes its impact on enterprise risk-taking, drawing the following conclusions: (1) SMEs’ synergistic transformation of digitization and greenization significantly promotes enterprise risk-taking. (2) The impact mechanism analysis finds that SMEs’ synergistic transformation of digitization and greenization improves enterprise risk-taking by reducing cash holdings and Research and Development (R&D) investment. (3) Further research finds that compared with state-owned SMEs, the synergistic transformation of digitization and greenization of non-state-owned SMEs has a more significant impact on enterprise risk-taking. Compared with high-tech SMEs, the synergistic transformation of digitization and greenization of non-high-tech SMEs has a more significant impact on enterprise risk-taking. These conclusions have practical significance for promoting SMEs’ synergistic transformation of digitization and greenization and improving enterprise risk-taking.